Performance of epoxy resin as self-healing agent - Mohd. Sam, Abdul Rahman (2015)
Formation of cracks due to the shrinkage effects during curing and mechanical loading can deteriorate the concrete performance especially in terms of durability aspect. Chemical and harsh solutions will easily penetrate into the concrete and cause damage to the concrete. In order to solve this problem, researchers have introduced a self-healing concrete; the mechanism of automatically repairing concrete cracks without external intervention. Nowadays, the self-healing concrete by using bacteria as a healing agent had gained interest among researchers. In contrast, this paper presents the study on performance of epoxy resin without hardener as a self-healing agent in concrete. Mortar specimens were prepared with mass ratio of 1:3 (cement: fine aggregates), water-cement ratio of 0.48 and 5 to 20% epoxy resin of cement content. All tested specimens were subjected to wet-dry curing; where compressive strength, apparent porosity and self-healing evaluation were measured. Result shows that, the compressive strength of mortar with addition of epoxy resin by 10% increased significantly compared to normal mortar. Epoxy resin as a healing agent was found to be functioned well as the compressive strength and ultrasonic pulse velocity regain the initial reading with prolonged curing time. These results together with microstructure test indicate that epoxy resin can be used as a self-healing agent.